A literatura de massa na perspectiva dialógica - Cortina, Arnaldo [UNESP] (My University, 2011)
Building on some core concepts of dialogic discourse analysis, this article aims to discuss, through an examination of the bestseller lists in Brazil during the years 2000 to 2010, the central features of contemporary mass literature. By the evidence of the prevalence of self-help books, we examine how the phenomenon is consisting. The conclusion that we get is that self-help can be seen both as a discourse genre and as style.

Tomando por base alguns conceitos centrais da análise dialógica do discurso, este artigo propõe discutir, por meio do exame das listas dos livros mais vendidos no Brasil durante os anos de 2000 a 2010, as características centrais da literatura de massa contemporânea. Por meio da constatação do predomínio dos livros de autoajuda, examina-se em que consiste esse fenômeno. O que se verifica é que a autoajuda pode ser observada tanto como gênero de discurso quanto como estilo.
Keywords: Alterity; Dialogism; Enunciation; Mass literature; Self-help; Alteridade; Autoajuda; Dialogismo; Enunciação; Literatura de massa